1985
DOI: 10.1177/154193128502900711
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Effectiveness of Warnings

Abstract: A paradigm was developed to examine the effectiveness of warnings in a laboratory task. A task was presented to subjects as one examining how people perform a basic chemistry demonstration. Experiment 1 examined the effects of two locations of the warning (before and after instructions) and two different signal word presentations (WARNING and Note). An additional condition with no warning or signal word served as a control. No effects were found on time or accuracy. However, compliance (use of mask and gloves)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Bansal-Travers et al 2011, Borland (1997), Braun and Silver (1995), Cvetkovich and Earle (1995), Dingus, Wreggit, and Hathaway (1993), Wogalter et al (1987) Text salience Conspicuous print, font color, font size, text direction, embeddedness in instruction text, highlighting text, white space Adams and Edworthy (1995), Barlow and Wogalter (1993), Frantz (1992), Hammond et al (2007), Malouff et al (1993), Strawbridge (1986a, b), Wogalter, Fontenelle, and Laughery (1985) Shape salience Conspicuousness of label configuration, shape of the label, package design, border width Adams and Edworthy (1995), Bhalla and Lastovicka (1984), Cvetkovich and Earle (1995), Barlow and Wogalter (1993), Goldberg et al (1999) , Strawbridge (1986a,b), Wogalter, Allison, and McKenna (1989) Picture Text versus picture, pictorial icons, visual information factor, graphic images Bansal-Travers et al 2011, Hassan et al (2007), Kees et al (2006Kees et al ( , 2010, Peters et al (2007), Sabbane, Lowrey, and Chebat (2009), Young and Wogalter (1990) subject filled out a questionnaire on smoking habits. Consequently, we propose the following: Laughery and Wogalter (2014) emphasize that understanding a warning does not necessarily ensure that it will be recalled at the proper time.…”
Section: Contextual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bansal-Travers et al 2011, Borland (1997), Braun and Silver (1995), Cvetkovich and Earle (1995), Dingus, Wreggit, and Hathaway (1993), Wogalter et al (1987) Text salience Conspicuous print, font color, font size, text direction, embeddedness in instruction text, highlighting text, white space Adams and Edworthy (1995), Barlow and Wogalter (1993), Frantz (1992), Hammond et al (2007), Malouff et al (1993), Strawbridge (1986a, b), Wogalter, Fontenelle, and Laughery (1985) Shape salience Conspicuousness of label configuration, shape of the label, package design, border width Adams and Edworthy (1995), Bhalla and Lastovicka (1984), Cvetkovich and Earle (1995), Barlow and Wogalter (1993), Goldberg et al (1999) , Strawbridge (1986a,b), Wogalter, Allison, and McKenna (1989) Picture Text versus picture, pictorial icons, visual information factor, graphic images Bansal-Travers et al 2011, Hassan et al (2007), Kees et al (2006Kees et al ( , 2010, Peters et al (2007), Sabbane, Lowrey, and Chebat (2009), Young and Wogalter (1990) subject filled out a questionnaire on smoking habits. Consequently, we propose the following: Laughery and Wogalter (2014) emphasize that understanding a warning does not necessarily ensure that it will be recalled at the proper time.…”
Section: Contextual Factorsmentioning
confidence: 99%
“…Appendix: Studies Included in the Meta-Analysis • Adams and Edworthy (1995)Azagba and Sharaf (2013) • Bansal-Travers et al 2011• Barlow and Wogalter (1993) • Bhalla and Lastovicka (1984) • Borland (1997)Braun and Silver (1995)Braun, Silver, and Stock (1992Godfrey, Rothstein, and Laughery (1985)Goldberg et al (1999) • Goldhaber and DeTurck (1988) • Goldhaber and DeTurck (1989)Goodall and Appiah (2008) • Hammond et al (2004 Wogalter, Allison, and McKenna (1989)Wogalter, Fontenelle, and Laughery (1985)Wogalter, Jarrard, and Simpson (1994) • Wogalter, Kalsher, and Racicot (1992) • Wogalter, Kalsher, and Racicot (1993)Wogalter et al (1987)Young and Wogalter (1990)Zhao et al (2014)…”
mentioning
confidence: 99%
“…Researchers have used a variety of measures to assess the effectiveness of warning labels in conveying hazard information to consumers. Common examples of the measures include noticeability (Frantz and Rhoades 1993), likelihood of reading (Magurno and Wogalter 1994), comprehension (Young and Wogalter 1990), recall (Lehto and Miller 1988), perceived hazard (Friedmann 1988; Otsubo 1988b), and behavioral intentions (Wogalter, Fontenelle, and Laughery 1985). In this research, we identify the five dimensions of effectiveness that represent the sequential processing of information that consumers engage in when they are exposed to warnings (McGuire 1980; Wogalter and Laughery 1996; Wogalter and Sojourner 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, the consumer may not see the warnings. For example, Wogalter, Fontenelle, & Laughery (1985) have shown that warnings located following a set of instructions may not be seen. A second possible reason is that consumers may not comprehend warnings.…”
Section: Introductionmentioning
confidence: 96%